Free-living physical activity and energy expenditure of rural children and adolescents in the Nandi region of Kenya. (9th July 2013) - Ojiambo, Robert; Gibson, Alexander R.; Konstabel, Kenn; Lieberman, Daniel E.; Speakman, John R.; Reilly, John J.; Pitsiladis, Yannis P.
Abstract: Purpose : To examine the relationship between physical activity and energy demands in children and adolescents with highly active lifestyles. Methods : Physical activity patterns of 30 rural Kenyan children and adolescents (14 ± 1 years, mean ± SD) with median body mass index (BMI) z -score = −1.06 [−3.29–0.67] median [range] were assessed by accelerometry over 1 week. Daily energy expenditure (DEE), activity-induced energy expenditure (AEE) and physical activity level (PAL) were simultaneously determined using doubly-labelled water (DLW). Active commuting to school was assessed by global positioning system. Results : Mean DEE, AEE and PAL were 12.2 ± 3.4, 5.7 ± 3.0 MJ/day and 2.3 ± 0.6, respectively. A model combining body mass, average accelerometer counts per minute and time in light activities predicted 45% of the variance in DEE ( p  < 0.05) with a standard error of DEE estimate of 2.7 MJ/day. Furthermore, AEE accounted for ∼47% of DEE. Distance to school was not related to variation in DEE, AEE or PAL and there was no association between active commuting and adiposity. Conclusion : High physical activity levels were associated with much higher levels of energy expenditure than observed in Western societies. These results oppose the concept of physical activity being stable and constrained in humans.